Big game [videorecording (DVD)] - Jackson, Samuel L.; Stevenson, Ray, 1964-; Garber, Victor; Huffman, Felicity, 1962-; Levine, Ted (Relativity : Anchor Bay Entertainment, 2015)
When Air Force One is shot down by terrorists leaving the President of the United States stranded in the wilderness, there is only one person around who can save him, a thirteen-year old boy called Oskari. In the forest on a hunting mission to prove his maturity to his family, Oskari had been planning to track down a deer, but instead discovers the most powerful man on the planet in an escape pod.